1992
DOI: 10.1037/0882-7974.7.3.367
|View full text |Cite
|
Sign up to set email alerts
|

Mental and physical health of spouse caregivers: The role of personality.

Abstract: Although personal resources of caregivers, such as coping skills and social support, have been shown to be important in understanding caregiver stress and health outcomes, personality traits have not previously been considered. The purpose of this study was to examine the association between the personality traits of neuroticism and dispositional optimism and mental and physical health outcomes. It was predicted that personality would have direct effects, and indirect effects through perceived stress, on healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
0
6

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(125 citation statements)
references
References 81 publications
(96 reference statements)
6
113
0
6
Order By: Relevance
“…Nevertheless, Beckham et al (1995) studied 65 rheumatoid arthritis patients and their caregivers and found that patient physical status was sttongly related to caregiver pessimism on the Life Orientation Test. Optimism has been associated with low levels of depression m caregivers (Sumi et al, 1997;Hinrichsen and Niederehe, 1994;Hooker et al, 1992). Fostering positive expectations may therefore lower levels of depression m caregivers.…”
Section: Dispositional Optimismmentioning
confidence: 99%
“…Nevertheless, Beckham et al (1995) studied 65 rheumatoid arthritis patients and their caregivers and found that patient physical status was sttongly related to caregiver pessimism on the Life Orientation Test. Optimism has been associated with low levels of depression m caregivers (Sumi et al, 1997;Hinrichsen and Niederehe, 1994;Hooker et al, 1992). Fostering positive expectations may therefore lower levels of depression m caregivers.…”
Section: Dispositional Optimismmentioning
confidence: 99%
“…Most studies include sociodemographic characteristics and social support within the caregiving situation, while a smaller group of studies has identified factors, such as patients' and partners' health prior to the care situation , quality of the relationship (e.g. marital satisfaction (Fuller and Swendsen, 1992) and personality factors, such as mastery (Pearlin et al, 1990), optimism and neuroticism (Hooker et al, 1992). Sociodemographic characteristics include variables like age, gender, living situation, type of relationship, and socioeconomic status of both the care recipient and caregiver.…”
Section: Contextual Factors In the Caregiving Processmentioning
confidence: 99%
“…Previous research has found that neuroticism is associated with more variability in laboratory-based cognitive performance (Robinson & Tamir, 2005). Neuroticism is also associated with increased perceived stress (e.g., Hooker, Monahan, Shifren, & Hutchinson, 1992) and heightened reactions to stressors (e.g., Mroczek & Almeida, 2004). Furthermore, neuroticism has been linked to cognitive performance, such that lower levels of neuroticism are related to better episodic memory performance (e.g., Meier, Perrig-Chiello, & Perrig, 2002).…”
mentioning
confidence: 99%